BUSINESS PROCESS MATURITY LEVEL DETERMINATION: A METHODOLOGICAL OUTLINE - Klimas, Darius (Ekonomika, 2011)
Extensive literature on business process management (BPM) suggests that organizations could enhance their overall performance by adopting a process view of business. Hammer (2007) states that, in virtually every industry, companies of all sizes have achieved extraordinary improvements in cost, quality, speed, profitability, and other key areas by focusing on, measuring and redesigning their customer-facing and internal processes. In reality, many things need to be changed to harness the power of processes, but how to ensure what exactly need to be changed, how much, and when? In the article, a methodologically extended Hammer’s business process maturity model framework and its methodological implementation guidelines are presented. The developed framework serves as a diagnostic tool for the identification of organization process maturity level and to do reasoned optimal improvements which lead to a better overall organization performance.